Time Driven Product Life Cycle Costing as A Cost Reduction Techniques: An Empirical Study in The General Company for Electrical and Electronic Industries - Mahdi Jawad Al-Kawaz, Salah; Abdul Alayma Aswad, Qusay (International Journal of Psychosocial Rehabilitation, 2020)
The cost reduction of a product or service is one of the most important means by which economic units operate to cope with the competitive situation in the current business environment. Cost management is based on modern techniques to reduce costs, and perhaps the most important of these modern techniques is the time driven product life cycle costing techniques (TD-PLCC). This paper seeks to focus on TD-PLCC techniques as one of the modern costs and management accounting techniques that have been developed in response to developments and changes that have occurred in the current business environment. The paper also aims to show how to benefit from it by the economic unit that seeks to manage cost by reducing it and enhancing competitive advantage, by finding ways and methods that contribute to reducing product costs. The results show that TDPLCC techniques provides more reliable information by identifying unused capacity (idle) and its costs and not loading it on the product. This, in turn, leads to the optimal use of capacity by the administration. Therefore, modern techniques should be adopted to calculate the cost and administration to keep pace with developments and changes in the current business environment.